Geological and geophysical evaluation of the Ajana area’s groundwater potential, southwestern Nigeria - O.M Ajibade; Adetayo F Folorunso; Stephen O Ariyo (Earth Sciences Research Journal)
Acombined geological and geophysical evaluation was madeof the groundwater potential of the Ajana, RemoNorth area in south-western Nigeria; the geology and other structural features of the rocks there strongly influenced and correlated the aquifers' storability and transmissivity. Geological mapping revealed that the area was made up of granite, quartzite and varieties of gneiss, some of which have good secondary porosity and permeability. Ten vertical electric soundings (VES) stations were established using a Schlumberger electrode array. Five geoelectric layers consisting of topsoil, sand, clayey-sandy, fractured / weathered basement and fresh bedrock were delineated. The aquifer layers were the 38.3m thick 283 ?m resistivity sand/sandy clay and 55 - 518 ?m resistivity fractured/weathered basement. Other geoelectric parameters used in evaluating the area's hydrogeological potential included curve type, anisotropy coefficient and reflection coefficient - The QH curve type was predominant in the area. The anisotropy Coefficients suggested VES stations having high groundwater potential ranging from 1.4 - 1.56; while the reflection coefficients for the area ranged from 0.21 - 0.99. The overall results showed that VES stations 8, 9 and 10 could be possible groundwater sources having high expected yield.